2015
DOI: 10.7747/jfes.2015.31.1.24
|View full text |Cite
|
Sign up to set email alerts
|

Status, Utilization and Economic Valuation of Non-timber Forest Products of Arunachal Pradesh, India

Abstract: Non-timber forest products are important component of subsistence and livelihood of tribal communities living in and near forests. This is of particular significance in the state of Arunachal Pradesh having more than 80% of geographical area under forest cover and predominantly inhabited by tribal people. Purpose of this study was to document the status and utilization pattern and to assess the economic value of NTFPs of the state. Present study was carried out in eight districts of Arunachal Pradesh viz., Cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 13 publications
1
15
0
Order By: Relevance
“…Our fi nding that the contribution of average net income from harvesting Cornelian cherry fruit to total average annual households' livelihood was 6.9 (ranging from of 3.6 to 7.3%) differs from that of Ghanbari et al (2011) who reported that in households with lower annual income, the proportion of income from fruit harvesting and sale to annual income was about 31%. Although a study on the contribution of non-timber forest products to annual income of the family has been reported to be more than fi fty percent (Sharma et al, 2015). In another investigation, Melaku et al (2014) found that the contribution of forest coffee, honey and spices was 47% of annual household income.…”
Section: Discussionmentioning
confidence: 96%
“…Our fi nding that the contribution of average net income from harvesting Cornelian cherry fruit to total average annual households' livelihood was 6.9 (ranging from of 3.6 to 7.3%) differs from that of Ghanbari et al (2011) who reported that in households with lower annual income, the proportion of income from fruit harvesting and sale to annual income was about 31%. Although a study on the contribution of non-timber forest products to annual income of the family has been reported to be more than fi fty percent (Sharma et al, 2015). In another investigation, Melaku et al (2014) found that the contribution of forest coffee, honey and spices was 47% of annual household income.…”
Section: Discussionmentioning
confidence: 96%
“…NTFPs based incomes vary across tribal households depending upon the degree of effort expended and contribute significantly to the total household income . The findings are not unusual and a significant number of studies (Salehi et al, 2010;Opaluwa et al, 2011;Singh and Quli, 2011;Saha and Sundriyal, 2012;Olaniyi et al, 2013;Bedia, 2014;Sharma et al, 2015;Islam and Quli, 2015;Shrey et al, 2017) across the world have demonstrated the dependency of forest dwellers on NTFPs for both subsistence and cash income.…”
Section: Exploitation Of Ntfps By the Tribal Householdsmentioning
confidence: 88%
“…The communities in the three villages are allowed to utilize non-timber forest products, but the har- vesting of timber from the mangroves is prohibited. Non-timber forest products are important component of subsistence and livelihood of communities living in and surrounding the forests (Sharma et al 2015). However, the utilization of the non-timber forest products was not optimally performed by the communities in the three villages.…”
Section: Social Capitalmentioning
confidence: 99%